2019
DOI: 10.1111/cobi.13334
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming human and large carnivore coexistence through institutional collaboration

Abstract: Achieving coexistence between large carnivores and humans in human‐dominated landscapes (HDLs) is a key challenge for societies globally. This challenge cannot be adequately met with the current sectoral approaches to HDL governance and an academic community largely dominated by disciplinary sectors. Academia (universities and other research institutions and organizations) should take a more active role in embracing societal challenges around conservation of large carnivores in HDLs by facilitating cross‐secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…Such activities may at some point require introduction of more collaborative approaches to support coexistence between humans and large carnivores in human-dominated landscapes [110]. As argued by Hartel et al [111], collaborative efforts should be strengthened by transdisciplinary research and active engagement of researchers in creating new institutional structures. Our case confirms that, in a favourable context, such collaboration between stakeholder groups and academia can have a significant impact on institutional dynamics.…”
Section: Plos Onementioning
confidence: 99%
“…Such activities may at some point require introduction of more collaborative approaches to support coexistence between humans and large carnivores in human-dominated landscapes [110]. As argued by Hartel et al [111], collaborative efforts should be strengthened by transdisciplinary research and active engagement of researchers in creating new institutional structures. Our case confirms that, in a favourable context, such collaboration between stakeholder groups and academia can have a significant impact on institutional dynamics.…”
Section: Plos Onementioning
confidence: 99%
“…Third, we found that highly relevant actors, such as farmers and decision-makers are less represented in research than others, such as managers, the general public and rural residents ( figure 2(a)). Human-carnivore research that overlooks the diversity of social actors involved in human-carnivore management can perpetuate and escalate the conflict with carnivores and create new social conflicts (Hartel et al 2019). To effectively promote coexistence, future research therefore should address the social causes underpinning conflicts, including human-human conflicts, the latter especially can be important but have often overlooked (Dickman 2010, Young et al 2010, Draheim et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Specific methods include collaborative learning, mental models, discursive approaches, and structure decision making (Chan et al 2012, Ban et al 2013. In addition, Hartel et al (2019) proposes to go beyond the simple inclusion of multiple actors and research the deeper levels of values and norms that underpin the actors' actions and behavior. By incorporating norms and values, but also through sustained collaboration with local actors, transdisciplinary approaches can therefore contribute to the long-term viability of humancarnivore coexistence (Hartel et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some contexts, population viability modeling and decision analysis provide valuable tools for projecting future populations states (Converse and Grant, 2019;Davis et al 2019). However, in many human-shaped landscapes these approaches may have limited practical applicability, particularly where natural and cultural values are threatened by various economic interests and conflicts between stakeholders regarding nature conservation goals are common (Hartel et al 2019). Furthermore, in certain cultures (e.g.…”
Section: Understand Socio-economic Drivers That Shape the Future Of Amentioning
confidence: 99%